A gyroscopic stabilizer to improve flutter performance of long-span cable-supported bridges. (1st August 2021) - Giaccu, Gian Felice; Caracoglia, Luca
Highlights: A gyroscopic stabilizer is studied to reduce propensity to long-span bridge flutter. Frequency-domain simulations at incipient aeroelastic instability are performed. Significant increment of critical flutter speed is noticed. Abstract: Long-span cable-supported bridges are gaining considerable importance in the world. It is generally recognized that long-span cable-supported bridges can be very sensitive to wind effects due to their aerodynamic properties and deck flexibility. Flutter is usually a major concern because it can lead to structural deck failure. This communication introduces a prototype of gyroscopic device as an active stabilizer for improving flutter performance. A mathematical model of the gyroscopic device, installed at the bridge deck level, was studied and implemented to assess its effectiveness in increasing the critical wind speed. A preliminary study was conducted to evaluate the stabilizer's performance on a benchmark long-span cable-supported bridge as a function of its gyricity. The results demonstrate that the gyroscopic stabilizer is very successful and bridge flutter threshold increases with the gyricity of the gyroscopic device, within a practical operational range.